PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) BERBANTUAN MEDIA VIDEO TERHADAP HASIL BELAJAR SISWA PADA MATERI LAJU REAKSI KELAS XI.IPA SMA NEGERI 1 SUNGAI AMBAWANG - Dewi Setiawati; Dedeh Kurniasih; Fitriani Fitriani (Jurnal Ilmiah Ar-Razi, 2016)
ABSTRACT This research had the purpose to find out the difference between the students’ learning outcomes which were taught by using NHT type of Cooperative Learning Method Assisted Video as Media and Lectures Method Assisted Video as Media as well as to find out how large the effect of NHT type of Cooperative Learning Method Assisted Video as Media in XI IPA class of SMA Negeri 1 Sungai Ambawang. This research was Quasi Experimental Research Nonequivalent Control Group Design. The sampling technique was saturated sample based on the students’ daily tests scores. The techniques of data collection used measurement, indirect observation and direct communication techniques. The data analysis result showed that the mean score of experimental class (72.50) was higher compared to the mean score of control class which was 60.50. Kolmogorov-Smirnov test resultsshowed that one class did not distribute normally so that it was done the statistical analysis using U-mannwhitneytest which obtained 0.028. This result was smaller than α(0.05) which meant that there was difference between experimental and control class. The calculation of effect size showed the value of 0.54 in moderate category and referred to the table Z which obtained 20.54% value. It showed that NHT type of Cooperative Learning Method Assisted Video as Media gave effect on students’ learning outcomes.Keywords : Learning Outcomes, The Reaction Rate, Numbered Heads Together (NHT)